Abatacept modulates CD80 and CD86 expression and memory formation in human B-cells - Lorenzetti, Raquel (2019)
Background: Cytotoxic T lymphocyte antigen-4 (CTLA-4) limits T-cell activation and is expressed on T-regulatory cells. Human CTLA-4 deficiency results in severe immune dysregulation. Abatacept (CTLA-4 Ig) is approved for the treatment of rheumatoid arthritis (RA) and its mechanism of action is attributed to effects on T-cells. It is known that CTLA-4 modulates the expression of its ligands CD80 and CD86 on antigen presenting cells (APC) by transendocytosis. As B-cells express CD80/CD86 and function as APC, we hypothesize that B-cells are a direct target of abatacept. Objectives: To investigate direct effects of abatacept on human B-lymphocytes in vitro and in RA patients. Methods: The effect of abatacept on healthy donor B-cells’ phenotype, activation and CD80/CD86 expression was studied in vitro. Nine abatacept-treated RA patients were studied. Seven of these were followed up to 24 months, and two up to 12 months only and treatment response, immunoglobulins, ACPA, RF concentrations, B-cell phenotype and ACPA-specific switched memory B-cell frequency were assessed. Results: B-cell development was unaffected by abatacept. Abatacept treatment resulted in a dose-dependent decrease of CD80/CD86 expression on B-cells in vitro, which was due to dynamin-dependent internalization. RA patients treated with abatacept showed a progressive decrease in plasmablasts and serum IgG. While ACPA-titers only moderately declined, the frequency of ACPA-specific switched memory B-cells significantly decreased. Conclusions: Abatacept directly targets B-cells by reducing CD80/CD86 expression. Impairment of antigen presentation and T-cell activation may result in altered B-cell selection, providing a new therapeutic mechanism and a base for abatacept use in B-cell mediated autoimmunity.